Wybrane czasopisma anglojęzyczne ze zbiorów Biblioteki Wydziału Prawa i Administracji UŁ jako źródło informacji o Unii Europejskiej - Witczak, Magdalena (Acta Universitatis Lodziensis. Folia Librorum, 2010)
The article describes the situation of scientific libraries in the modern world. Its aim is to show how the Polish academic libraries could participate in the process of sharing materials about the European Union. It is possible by setting the example of the activity of chosen academic institution like the Library of the Department of Law and Administration of the University of Lodz (UŁ). It stores and spreads international journals connected with law, economics and other social branches of science. In the article we focus on some English journals devoted to the cases of the European Union. By the analysis of their contents we may familiarize with the offer of the library in this matter. It is important that students, lecturers and others were aware of the possibilities created for them by the library. The article presents the library as a place where all their readers could find complete information about the European Union, even in the international sources like English journals.